MRI evaluation of body composition changes in wrestlers undergoing rapid weight loss - Kukidome, T.; Shirai, K.; Kubo, J.; Matsushima, Y.; Yanagisawa, O.; Homma, T.; Aizawa, K. (British Journal of Sports Medicine, 2008)
Purpose: Changes in body composition of college wrestlers undergoing rapid weight reduction were evaluated over time using magnetic resonance imaging (MRI).